E-Logbook Application System to Support the Guidance Process Final Assignment for Semarang Maritime Science Polytechnic Cadets - Mariana Kristiyanti; Akhmad Ndori; Muchamad Imroni Mubin; Bayu Arya Pamungkas; Setiangga Fachrurrozi (International Journal of Economics and Management Sciences, 2024)
A website-based application system that is one of the Internet media that is often used to do various things by providing services ease, speed especially in the recording process. The Polytechnic of Navigation Sciences (PIP) Semarang, previously still used manual methods in the process of guiding the Final Tasks (scripts) of its tarun. Given the current advances in information technology, the manual can be improved to anticipate problems in the guidance process, for example, the missing or missing guidance records can be minimized by using an application system. For this, it is necessary to build an e-logbook application system that can input data from a manual system to a website-based application system aimed at managing data and storing data as well as building a system which can facilitate the performance of the lecturer and the study program performance at the Polytechnic of Shipping Science (PIP) Semarang. The objective of this research is to develop a website based application system such as e-logbook to make the process of recording the final guidance activities of the cadets easier. This research uses the type of qualitative data with data collection in the form of interviews with tutoring lecturers and cadets in PIP Semarang, observation and literature studies. The utilities used in the development of this system are PHP and MySQL. The research resulted in an e-logbook system that is easily accessible to various stakeholders in the Semarang Polytechnic of Shipping Sciences (PIP) environment that includes structured recording, storage, and reporting.